Signal-Processing Strategy for Restoration of Cross-Channel Suppression in Hearing-Impaired Listeners - Rasetshwane, Daniel M.; Gorga, Michael P.; Neely, Stephen T. (IEEE transactions on biomedical engineering, 2014)
Because frequency components interact nonlinearly with each other inside the cochlea, the loudness growth of tones is relatively simple in comparison to the loudness growth of complex sounds. The term suppression refers to a reduction in the response growth of one tone in the presence of a second tone. Suppression is a salient feature of normal cochlear processing and contributes to psychophysical masking. Suppression is evident in many measurements of cochlear function in subjects with normal hearing, including distortion-product otoacoustic emissions (DPOAEs). Suppression is also evident, to a lesser extent, in subjects with mild-to-moderate hearing loss. This paper describes a hearing-aid signal-processing strategy that aims to restore both loudness growth and two-tone suppression in hearing-impaired listeners. The prescription of gain for this strategy is based on measurements of loudness by a method known as categorical loudness scaling. The proposed signal-processing strategy reproduces measured DPOAE suppression tuning curves and generalizes to any number of frequency components. The restoration of both normal suppression and normal loudness has the potential to improve hearing-aid performance and user satisfaction.